How Might India’s Public Health Systems Be Strengthened? - Das Gupta, Monica; Shukla, Rajendra; Somanathan, T.V.; Datta, K.K. (2012)
The central government s policies, though well-intentioned, have inadvertently de-emphasized environmental health and other preventive public health services in India since the 1950s, when it was decided to amalgamate the medical and public health services and to focus public health services largely on single-issue programs. This paper discusses how successive policy decisions have diminished the Health Ministry s capacity for stewardship of the nation s public health. These decisions have introduced policies and fiscal incentives that have inadvertently enabled states to prioritize medical services and single-issue programs over broader public health services, and diminished the capacity of the public health workforce to deliver public health services. Diseases resulting from poor environmental health conditions continue to impose high costs even among the more affluent, and hinder development. There are many approaches to strengthening the public health system, and the authors suggest one that may require relatively little modification of existing structures and systems. They suggest establishing a focal point in the Health Ministry for public health stewardship, and re-vitalizing the states public health managerial cadres as well as the grassroots public health workers. The central government could consider linking its fiscal support to states with phased progress in four areas: (1) the enactment of state Public Health Acts; (2) the establishment by states of separate public health directorates; (3) the re-vitalization of grassroots public health workers; and (4) health department engagement in ensuring municipal public health. The central focal point could provide the needed support, oversight, incentives, and sanctions to ensure that states build robust public health systems. These measures can do much to help governments use public funds more effectively for protecting people s health.